Weather Downtime And Its Effect On Fishing Operation In Peninsular Malaysia - Yaakob, Omar (Penerbit UTM Press, 2005)

(untitled)
This Paper Presents The Results Of A Study Of The Effect Of Weather Downtime On The Fishing Industry In Peninsular Malaysia. The Study Was Carried Out With The Aim Of Establishing A Clearer Relationship Between Weather And Fishing Operation, Especially During Monsoon Season. This Paper Focused On The Wind And Wave Pattern And Their Effects On Fishing Boat Operability, Fish Landing, Fish Availability, And Price. The Effect On The Fishermen Activity And Income As A Result Of The Weather Down Time Was Also Discussed. The Result Of The Study Has Indicated That There Is A Close Relationship Between Weather And Fishing Operation As Well As Fishermen’s Income. The Study Also Concluded That Weather Has Been Significantly Affecting The East Coast Fishermen Compared With Their West Coast Counterparts.